Practice patterns of adjuvant radiotherapy in women with stage I to II endometrial carcinoma: a real-world multi-institutional analysis in China - Wenhui Wang; Tiejun Wang; Zi Liu; Jianli He; Xiaoge Sun; Wei Zhong; Fengjv Zhao; Xiaomei Li; Sha Li; Hong Zhu; Zhanshu Ma; Ke Hu; et al. (BMC, 2023)
Abstract Background This study aimed to report clinical practice patterns of postoperative radiotherapy for stage I to II endometrial carcinoma (EC) patients treated in 13 Chinese medical centers. Methods We included early stage EC patients treated by hysterectomy and adjuvant RT between 2003 and 2017 from 13 institutions. Patients were classified into 4 risk groups based on ESMO-ESGO-ESTRO recommendations (2014). Results A total of 1,227 cases were analyzed. Along the 15 years of the study, an increasing tendency was found towards administration for vaginal brachytherapy (VBT) alone, while the proportion of external beam pelvic radiotherapy (EBRT) alone remained stable in the corresponding period. When radiation modalities were stratified by risk groups, proportion of VBT alone significantly increased in all risk groups. The higher the risk, the later VBT became the main adjuvant treatment modality. However, EBRT alone or with VBT remained the main adjuvant method for high-risk patients. There were 13 dose-fractionation schemes for VBT alone with the scheme of 30 Gy in 6 fractions prescribed at 0.5cm under the vaginal mucosa accounting for most. There were 17 schemes for VBT boost and the most common schedule was 10 Gy in 2 fractions. The upper 3-5cm part of vagina was the most frequent target. 89.6% of the practitioners performed two-dimensional VBT technique. The median dose for EBRT was 50 Gy. From 2003 to 2017, conventional radiotherapy was gradually replaced by three-dimensional conformal radiotherapy modality and intensity modulated radiotherapy. Conclusion We report a significant shift from EBRT to VBT alone for high-intermediate-risk, intermediate-risk and low-risk EC patients from 2003 to 2017 while EBRT remained the main radiation modality for high-risk early stage patients. There has been remarkable heterogeneity among VBT dose fractionation schedules across China. Trial registration The clinical trial ID was ChiCTR-PRC-17010712. It was authorized by the Institutional Review Board of Peking Union Medical College Hospital (N0. S-K139).